The Impact of Physical Education Learning on Healthy Life Style Knowledge of Elementary School Students - Friskawati, Gita Febria; Santosa, Agus; Sanjaya, Reza (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
Healthy lifestyle knowledge becomes a foundation that should be owned by elementary school students to improve their life wellbeing level in the future. This research aimed to find out the impact of Physical Education learning on the healthy life style knowledge of elementary school students. The research used an ex-post facto descriptive method on the population consisting of 112 grade six students of elementary public schools in Cimahi City. The samples of the study were 78 elementary students chosen through a convenience sampling technique. The instrument used was The Clean and Healthy Behavior Scale (TCHBS) with the reliability p=0.87. The data analysis used a descriptive percentage and one sample t-test on the SPSS 19.0 program. The result shows that the Physical Education instruction significantly affects the healthy life style knowledge of elementary school students, mostly on the student knowledge of dietary habit and physical activity.Â  The healthy lifestyle knowledge of elementary school students was not merely the responsibility of Physical Education teachers, but also their parents and surroundings. A further research is needed to examine the effectiveness of Physical Education program related to the school support and gender in improving knowledge as well as to implement the healthy lifestyle of the students.